Molecular sieve catalyst, preparation method thereof and application of molecular sieve catalyst in reaction for preparing acrolein through glycerol dehydration
By using a multi-stage pore ZSM-5 molecular sieve catalyst and adding additives, and combining alkali treatment-acid treatment combined with post-treatment method, the problem of low conversion and selectivity of existing catalysts in the reaction to produce acrolein by dehydrating glycerine, and catalytic effects of high conversion, selectivity and stability are achieved.
Patent Information
- Application Number
- CN202311765031.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-20
- Publication Date
- 2025-06-20
AI Technical Summary
The existing catalysts have low conversion and selectivity in the reaction to produce acrolein by dehydrating glycerin, and are not stable enough, making it difficult to meet the needs of industrial production.
A multi-stage pore ZSM-5 molecular sieve catalyst was used and prepared by alkali-acid treatment combined with post-treatment method. Add additives such as Zn, Mg, and Ca to form a multi-stage pore ZSM-5 molecular sieve catalyst, which was used to prepare acrolein reaction for dehydration of glycerol.
The conversion rate, selectivity and catalyst stability of the reaction of glycerol dehydration to produce acrolein is significantly improved, and the high conversion rate and selectivity can be maintained for more than 300 hours.
Abstract
Description
Technical Field
[0001] The present application relates to a molecular sieve catalyst, a preparation method thereof, and an application in the reaction of glycerol dehydration to acrolein, belonging to the field of catalyst synthesis materials. Background Art
[0002] Acrolein is the simplest unsaturated aldehyde with active chemical properties and is an important chemical intermediate. Acrolein is mainly used in the synthesis of chemicals such as acrylic acid, 1,3-propanediol, and feed additive methionine. Glycerol is a by-product of the biodiesel industry, and 10 wt% of the total biodiesel production will be produced as by-product glycerol during the industrial production of biodiesel. It is feasible to produce acrolein from the by-product glycerol in the production process of biodiesel. On the one hand, it can reduce the production cost of biodiesel and improve the overall competitiveness of the biodiesel industry; on the other hand, it can increase the added value of glycerol. CN 201310459066 discloses a mesoporous ZSM-5 molecular sieve catalyst, but its conversion rate decreases rapidly. CN 201310735105 discloses a hierarchical pore ZSM-5 molecular sieve as a glycerol dehydration catalyst, and the selectivity of acrolein is 83-87%, but the conversion rate of glycerol is only about 80%. Therefore, developing a catalyst with high glycerol conversion rate and acrolein selectivity and high stability is still a problem to be solved in this process. Summary of the Invention
[0003] The present application provides a catalyst for glycerol dehydration to acrolein and a preparation method thereof. The catalyst has high conversion rate, selectivity and stability for the reaction system of glycerol dehydration to acrolein.
[0004] In one aspect of the present application, a molecular sieve catalyst is provided, and the molecular sieve catalyst includes a hierarchical pore molecular sieve and an additive;
[0005] The hierarchical pore molecular sieve is a hierarchical pore ZSM-5 molecular sieve;
[0006] The pore size distribution of the hierarchical pore ZSM-5 molecular sieve is in the range of 10-30 nm;
[0007] The additive includes an additive element, and the additive element is selected from at least one of Zn, Mg, and Ca;
[0008] The content of the additive is 0.1-2 wt% of the mass of the molecular sieve catalyst.
[0009] Optionally, the pore size of the hierarchical pore ZSM-5 molecular sieve is independently selected from any value of 10 nm, 12 nm, 15 nm, 18 nm, 23 nm, 25 nm, 30 nm or any range value between any two of the above.
[0010] Optionally, the mass content of the auxiliary agent in the molecular sieve catalyst independently selects any value from 0.1 wt%, 0.2 wt%, 0.5 wt%, 1 wt%, 1.5 wt%, 2 wt% or any range value between any two of the above.
[0011] Another aspect of the present application provides a preparation method of the above molecular sieve catalyst, including the following steps:
[0012] Impregnate the post-treated hierarchical pore ZSM-5 molecular sieve into an aqueous solution containing a precursor of the auxiliary agent element, dry, and calcine I to obtain the molecular sieve catalyst;
[0013] The post-treatment is a combined use of alkali treatment and acid treatment, including: the microporous ZSM-5 molecular sieve is alkali-treated in an alkali solution, dried I to obtain solid I; solid I is acid-treated in an acid solution, dried II and calcined II to obtain solid II; solid II is ion-exchanged in an ammonium salt solution, dried III and calcined III to obtain the hierarchical pore ZSM-5 molecular sieve.
[0014] Optionally, the precursor of the auxiliary agent element selects at least one of Zn(NO3)2, Mg(NO3)2, Ca(NO3)2;
[0015] The solid-liquid ratio of the hierarchical pore ZSM-5 molecular sieve to the aqueous solution containing the precursor of the auxiliary agent element is 1:2 to 1:10 g / ml.
[0016] Optionally, the solid-liquid ratio independently selects any value from 1:2 g / ml, 1:5 g / ml, 1:8 g / ml, 1:10 g / ml or any range value between any two of the above.
[0017] Optionally, the impregnation time is 5 to 24 hours, and the impregnation temperature is 20 to 50 °C;
[0018] The temperature of the calcination I is 400 to 600 °C, the time of the calcination I is 1 to 6 hours, and the calcination I is carried out in an oxygen-containing atmosphere.
[0019] Optionally, the temperature of the calcination I independently selects any value from 400 °C, 450 °C, 500 °C, 550 °C, 600 °C or any range value between any two of the above.
[0020] Optionally, the time of the calcination I independently selects any value from 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours or any range value between any two of the above.
[0021] Optionally, the drying is carried out at 60 to 120 °C for 10 to 24 hours.
[0022] Optionally, the silica-alumina ratio of the microporous ZSM-5 molecular sieve is Si / Al = 20 to 50.
[0023] Optionally, the silica-alumina ratio of the microporous ZSM-5 molecular sieve is independently selected from any value among 20, 30, 40, 50 or any range value between any two of the above.
[0024] Optionally, the alkali solution is selected from one of KOH, NaOH, and Na2CO3;
[0025] The concentration of the alkali solution is 0.1 to 0.4 mol / L;
[0026] The conditions for the alkali treatment include: stirring at 60 to 80 °C for 15 to 30 min;
[0027] The temperature for the first drying is 80 to 120 °C, and the time for the first drying is 12 to 36 h.
[0028] Optionally, the concentration of the alkali solution is independently selected from any value among 0.1 mol / L, 0.15 mol / L, 0.2 mol / L, 0.3 mol / L, 0.4 mol / L or any range value between any two of the above.
[0029] Optionally, the acid in the acid solution is selected from at least one of acetic acid, oxalic acid, hydrochloric acid, and nitric acid;
[0030] The concentration of the acid solution is 0.1 mol / L to 2 mol / L.
[0031] The conditions for the acid treatment include: stirring at 60 to 100 °C for 2 to 8 h;
[0032] The temperature for the second drying is 100 °C, and the time for the second drying is 10 to 24 h;
[0033] The temperature for the second calcination is 450 to 600 °C, and the time for the second calcination is 2 to 5 h.
[0034] Optionally, the concentration of the acid solution is independently selected from any value among 0.1 mol / L, 0.5 mol / L, 1 mol / L, 1.5 mol / L, 2 mol / L or any range value between any two of the above.
[0035] Optionally, the ammonium salt in the ammonium salt solution is selected from one of NH4NO3 and NH4Cl;
[0036] The concentration of the ammonium salt solution is 0.1 to 2 mol / L;
[0037] The temperature for the third drying is 100 °C, and the time for the third drying is 12 to 36 h;
[0038] The temperature of the third calcination is 450 to 600 °C, and the time of the third calcination is 3 to 6 h.
[0039] Optionally, the concentration of the ammonium salt solution is independently selected from any value of 0.1 mol / L, 0.5 mol / L, 1 mol / L, 1.5 mol / L, 2 mol / L or any range value between any two of the above.
[0040] As a specific embodiment, the preparation method of the molecular sieve catalyst includes:
[0041] Preparing a hierarchical pore molecular sieve by a post-treatment method, making the promoter into an aqueous solution, adding the hierarchical pore molecular sieve into the solution for impregnation and calcination to obtain the catalyst;
[0042] The post-treatment method is the combined use of alkali treatment and acid treatment;
[0043] The alkali treatment-acid treatment includes: treating microporous ZSM-5 molecular sieve in an alkali solution, washing and drying to obtain solid I; treating solid I in an acid solution, washing, drying and calcining to obtain solid II; treating solid II in an ammonium salt solution, washing, drying and calcining to obtain the hierarchical pore ZSM-5 molecular sieve.
[0044] In another aspect of the present application, a method for dehydrating glycerol to acrolein is provided. A raw material containing an aqueous glycerol solution is introduced into a reactor and reacted in contact with a catalyst;
[0045] The catalyst is the above-mentioned molecular sieve catalyst.
[0046] Optionally, the method includes pre-treating the catalyst;
[0047] The conditions for the pre-treatment are: pre-treating at 450 °C under a nitrogen atmosphere.
[0048] Optionally, in the aqueous glycerol solution, the mass concentration of glycerol is 10 to 40 wt%.
[0049] Optionally, the mass space velocity of the raw material is 0.1 to 3.0 g·g -1 ·h -1 。
[0050] Optionally, the reaction temperature is 250 to 500 °C.
[0051] Optionally, the mass concentration of the oil is independently selected from any value of 10 wt%, 20 wt%, 30 wt%, 40 wt% or any range value between any two of the above.
[0052] Optionally, the mass hourly space velocity of the raw material is independently selected from any value of 0.1 g·g -1 ·h -1 , 0.5 g·g -1 ·h -1 , 1 g·g -1 ·h -1 , 1.5 g·g -1 ·h -1 , 2 g·g -1 ·h -1 , 2.5 g·g -1 ·h -1 , 3 g·g -1 ·h -1 or any range value between any two of the above.
[0053] Optionally, the reaction temperature is independently selected from any value of 250 °C, 350 °C, 450 °C, 500 °C or any range value between any two of the above.
[0054] Optionally, the reaction pressure is atmospheric pressure.
[0055] Optionally, the reactor is a fixed-bed reactor.
[0056] The beneficial effects that can be produced by this application include:
[0057] (1) This application provides a catalyst for glycerol dehydration to produce acrolein and a preparation method thereof. The catalyst preparation method is simple and the cost is low.
[0058] (2) The above catalyst provided by this application has high conversion rate, selectivity and stability for the reaction of glycerol dehydration to produce acrolein. Detailed implementation mode
[0059] The following describes this application in detail with reference to the examples, but this application is not limited to these examples.
[0060] Unless otherwise specified, the raw materials used in this application are all commercially purchased and used directly without special treatment.
[0061] The product analysis was carried out on an Agilent 7890B gas chromatograph with an FID detector and a PLOT / Q chromatographic column for analysis.
[0062] Example 1
[0063] Weigh 12 g of HZSM-5 zeolite (Si / Al = 30) and add it to 360 ml of 0.15 mol / L NaOH solution. Stir at 65 °C for 30 min, centrifuge and wash until neutral, then dry at 100 °C for 12 h to obtain solid I. Take 8 g of solid I and add it to 80 ml of 0.1 mol / L acetic acid solution. Stir at 60 °C for 5 h, then place it in an oven and dry at 100 °C for 12 h. After drying, calcine the sample at 550 °C for 3 h to obtain solid II. Take 6 g of solid II and add it to 120 ml of 1 mol / L NH4NO3 solution. Perform ion exchange three times at 85 °C, centrifuge and wash, dry at 100 °C for 12 h, and finally calcine at 550 °C for 3 h to obtain hierarchical pore ZSM-5 zeolite. Dissolve 0.02 g of Zn(NO3)2 . 6H2O in 10 ml of deionized water, impregnate it onto 2 g of hierarchical pore ZSM-5 zeolite, stir at 25 °C for 8 h, then dry at 100 °C for 12 h. Subsequently, calcine it at 550 °C in an air atmosphere for 3 h. Crush and tablet the calcined catalyst into 20 - 40 mesh particles. Take 0.5 g and load it into a fixed-bed reactor, and pretreat the catalyst with nitrogen at 450 °C. When the reactor temperature drops to 350 °C, introduce a 20 wt% glycerol aqueous solution with a mass space velocity of 1.5 g·g -1 ·h -1 . The conversion rate of glycerol is 99%, the selectivity of acrolein is 95%, and the conversion rate greater than 95% is maintained for 300 hours. It can be known from nitrogen physical adsorption analysis that the pore diameter of the hierarchical pore ZSM-5 zeolite is 12 nm and the content of the promoter is 0.2 wt%
[0064] Example 2
[0065] Weigh 12 g of HZSM-5 zeolite (Si / Al = 30) and add it to 360 ml of 0.2 mol / L NaOH solution. Stir at 65 °C for 30 min, centrifuge and wash until neutral, then dry at 100 °C for 12 h to obtain solid I. Take 8 g of solid I and add it to 80 ml of 0.1 mol / L acetic acid solution. Stir at 60 °C for 5 h, then place it in an oven and dry at 100 °C for 12 h. After drying, calcine the sample at 550 °C for 3 h to obtain solid II. Take 6 g of solid II and add it to 120 ml of 1 mol / L NH4NO3 solution. Perform ion exchange three times at 85 °C, centrifuge and wash, dry at 100 °C for 12 h, and finally calcine at 550 °C for 3 h to obtain hierarchical pore ZSM-5 zeolite. Dissolve 0.09 g of Zn(NO3)2 .6H2O was dissolved in 10 ml of deionized water and impregnated onto 2 g of hierarchical ZSM-5 zeolite. It was stirred at 25 °C for 8 h, then dried at 100 °C for 12 h, and subsequently calcined in air atmosphere at 550 °C for 3 h. The calcined catalyst was crushed and pressed into 20 - 40 mesh particles. 0.5 g of the catalyst was loaded into a fixed-bed reactor and pretreated with nitrogen at 450 °C. When the reactor temperature dropped to 350 °C, a 20 wt% glycerol aqueous solution was introduced with a mass space velocity of 1.5 g·g -1 ·h -1 , the conversion rate of glycerol was 99%, the selectivity of acrolein was 94%, and the conversion rate greater than 95% was maintained for 350 h. It was known from nitrogen physical adsorption analysis that the pore diameter of the hierarchical ZSM-5 zeolite was 15 nm and the content of the promoter was 1 wt%
[0066] Example 3
[0067] 12 g of HZSM-5 zeolite (Si / Al = 30) was weighed and added to 360 ml of 0.2 mol / L NaOH solution. It was stirred at 65 °C for 30 min, centrifuged and washed until neutral, and dried at 100 °C for 12 h to obtain solid I; 8 g of solid I was added to 80 ml of 0.5 mol / L nitric acid solution, stirred at 60 °C for 5 h, then placed in an oven and dried at 100 °C for 12 h. The dried sample was calcined at 550 °C for 3 h to obtain solid II; 6 g of solid II was added to 120 ml of 1 mol / L NH4NO3 solution, and ion exchange was carried out 3 times at 85 °C, centrifuged and washed, dried at 100 °C for 12 h, and finally calcined at 550 °C for 3 h to obtain hierarchical ZSM-5 zeolite. 0.09 g of Zn(NO3)2 . 6H2O was dissolved in 10 ml of deionized water and impregnated onto 2 g of hierarchical ZSM-5 zeolite. It was stirred at 25 °C for 8 h, then dried at 100 °C for 12 h, and subsequently calcined in air atmosphere at 550 °C for 3 h. The calcined catalyst was crushed and pressed into 20 - 40 mesh particles. 0.5 g of the catalyst was loaded into a fixed-bed reactor and pretreated with nitrogen at 450 °C. When the reactor temperature dropped to 350 °C, a 20 wt% glycerol aqueous solution was introduced with a mass space velocity of 1.5 g·g -1 ·h -1 , the conversion rate of glycerol was 99%, the selectivity of acrolein was 95%, and the conversion rate greater than 95% was maintained for 420 h. It was known from nitrogen physical adsorption analysis that the pore diameter of the hierarchical ZSM-5 zeolite was 18 nm and the content of the promoter was 1 wt%
[0068] Example 4
[0069] Weigh 12 g of HZSM-5 molecular sieve (Si / Al = 30) and add it to 360 ml of 0.2 mol / L NaOH solution. Stir at 65 °C for 30 min, centrifuge and wash until neutral, then dry at 100 °C for 12 h to obtain solid I. Take 8 g of solid I and add it to 80 ml of 0.5 mol / L nitric acid solution. Stir at 60 °C for 5 h, then place it in an oven and dry at 100 °C for 12 h. After drying, calcine the sample at 550 °C for 3 h to obtain solid II. Take 6 g of solid II and add it to 120 ml of 1 mol / L NH4NO3 solution. Conduct ion exchange 3 times at 85 °C, centrifuge and wash, dry at 100 °C for 12 h, and finally calcine at 550 °C for 3 h to obtain hierarchical pore ZSM-5 molecular sieve. Dissolve 0.21 g of Mg(NO3)2 . 6H2O in 10 ml of deionized water, impregnate it onto 2 g of hierarchical pore ZSM-5 molecular sieve, stir at 25 °C for 8 h, then dry at 100 °C for 12 h. Subsequently, calcine it at 550 °C in an air atmosphere for 3 h. Crush and tablet the calcined catalyst into 20 - 40 mesh particles. Take 0.5 g and load it into a fixed-bed reactor, and pretreat the catalyst with nitrogen at 450 °C. When the reactor temperature drops to 350 °C, introduce a 20 wt% glycerol aqueous solution, with a mass space velocity of 1.5 g·g -1 ·h -1 . The conversion rate of glycerol is 98%, the selectivity of acrolein is 92%, and the conversion rate greater than 95% is maintained for 380 h. It can be known from nitrogen physical adsorption analysis that the pore diameter of the hierarchical pore ZSM-5 molecular sieve is 18 nm, and the content of the promoter is 1 wt%
[0070] Example 5
[0071] Weigh 12 g of HZSM-5 molecular sieve (Si / Al = 30) and add it to 360 ml of 0.2 mol / L NaOH solution. Stir at 65 °C for 30 min, centrifuge and wash until neutral, then dry at 100 °C for 12 h to obtain solid I. Take 8 g of solid I and add it to 80 ml of 0.5 mol / L nitric acid solution. Stir at 60 °C for 5 h, then place it in an oven and dry at 100 °C for 12 h. After drying, calcine the sample at 550 °C for 3 h to obtain solid II. Take 6 g of solid II and add it to 120 ml of 1 mol / L NH4NO3 solution. Conduct ion exchange 3 times at 85 °C, centrifuge and wash, dry at 100 °C for 12 h, and finally calcine at 550 °C for 3 h to obtain hierarchical pore ZSM-5 molecular sieve. Dissolve 0.12 g of Ca(NO3)2 .4H2O was dissolved in 10 ml of deionized water, impregnated onto 2 g of hierarchical ZSM-5 zeolite, stirred at 25 °C for 8 h, then dried at 100 °C for 12 h, and subsequently calcined in air atmosphere at 550 °C for 3 h. The calcined catalyst was crushed and pressed into 20-40 mesh particles, and 0.5 g was loaded into a fixed-bed reactor and pretreated with nitrogen at 450 °C. When the reactor temperature dropped to 350 °C, a 20 wt% glycerol aqueous solution was fed with a mass space velocity of 1.5 g·g -1 ·h -1 , the conversion of glycerol was 99%, the selectivity to acrolein was 93%, and the conversion greater than 95% was maintained for 470 h. Physical adsorption analysis using nitrogen showed that the pore size of the hierarchical ZSM-5 zeolite was 18 nm and the content of the promoter was 1 wt%
[0072] Example 6
[0073] 12 g of HZSM-5 zeolite (Si / Al = 30) was weighed and added to 360 ml of 0.3 mol / L NaOH solution, stirred at 65 °C for 30 min, centrifuged and washed until neutral, and dried at 100 °C for 12 h to obtain solid I; 8 g of solid I was added to 80 ml of 0.5 mol / L nitric acid solution, stirred at 60 °C for 5 h, then placed in an oven and dried at 100 °C for 12 h, and the dried sample was calcined at 550 °C for 3 h to obtain solid II; 6 g of solid II was added to 120 ml of 1 mol / L NH4NO3 solution, and ion exchange was carried out 3 times at 85 °C, centrifuged and washed, dried at 100 °C for 12 h, and finally calcined at 550 °C for 3 h to obtain hierarchical ZSM-5 zeolite. 0.12 g of Zn(NO3)2 . 4H2O was dissolved in 10 ml of deionized water, impregnated onto 2 g of hierarchical ZSM-5 zeolite, stirred at 25 °C for 8 h, then dried at 100 °C for 12 h, and subsequently calcined in air atmosphere at 550 °C for 3 h. The calcined catalyst was crushed and pressed into 20-40 mesh particles, and 0.5 g was loaded into a fixed-bed reactor and pretreated with nitrogen at 450 °C. When the reactor temperature dropped to 350 °C, a 20 wt% glycerol aqueous solution was fed with a mass space velocity of 1.5 g·g -1 ·h -1 , the conversion of glycerol was 99%, the selectivity to acrolein was 94%, and the conversion greater than 95% was maintained for 600 h. Physical adsorption analysis using nitrogen showed that the pore size of the hierarchical ZSM-5 zeolite was 23 nm and the content of the promoter was 1.5 wt%
[0074] Example 7
[0075] Weigh 12 g of HZSM-5 zeolite (Si / Al = 30) and add it to 360 ml of 0.3 mol / L NaOH solution. Stir at 65 °C for 30 min, centrifuge and wash until neutral, then dry at 100 °C for 12 h to obtain solid I. Take 8 g of solid I and add it to 80 ml of 0.5 mol / L nitric acid solution. Stir at 60 °C for 5 h, then place it in an oven and dry at 100 °C for 12 h. After drying, calcine the sample at 550 °C for 3 h to obtain solid II. Take 6 g of solid II and add it to 120 ml of 1 mol / L NH4NO3 solution. Conduct ion exchange 3 times at 85 °C, centrifuge and wash, dry at 100 °C for 12 h, and finally calcine at 550 °C for 3 h to obtain hierarchical pore ZSM-5 zeolite. Dissolve 0.05 g of Zn(NO3)2 . ·6H2O and 0.12 g of Mg(NO3)2 . ·6H2O in 10 ml of deionized water, impregnate it onto 2 g of hierarchical pore ZSM-5 zeolite, stir at 25 °C for 8 h, then dry at 100 °C for 12 h, and subsequently calcine in air atmosphere at 550 °C for 3 h. Crush and tablet the calcined catalyst into particles of 20 - 40 mesh. Take 0.5 g and load it into a fixed-bed reactor, and pre-treat the catalyst with nitrogen at 450 °C. When the reactor temperature drops to 350 °C, introduce 20 wt% glycerol aqueous solution, with a mass space velocity of 1.5 g·g -1 ·h -1 . The conversion rate of glycerol is 99%, the selectivity of acrolein is 94%, and the conversion rate remains above 95% for 600 hours. It can be known from nitrogen physical adsorption analysis that the pore diameter of the hierarchical pore ZSM-5 zeolite is 23 nm, and the total content of the promoter is 1 wt% (Zn and Mg each account for 0.5 wt%)
[0076] Example 8
[0077] Weigh 12 g of HZSM-5 zeolite (Si / Al = 30) and add it to 360 ml of 0.3 mol / L NaOH solution. Stir at 65 °C for 30 min, centrifuge and wash until neutral, then dry at 100 °C for 12 h to obtain solid I. Take 8 g of solid I and add it to 80 ml of 0.5 mol / L nitric acid solution. Stir at 60 °C for 5 h, then place it in an oven and dry at 100 °C for 12 h. After drying, calcine the sample at 550 °C for 3 h to obtain solid II. Take 6 g of solid II and add it to 120 ml of 1 mol / L NH4NO3 solution. Conduct ion exchange 3 times at 85 °C, centrifuge and wash, dry at 100 °C for 12 h, and finally calcine at 550 °C for 3 h to obtain hierarchical pore ZSM-5 zeolite. Dissolve 0.06 g of Ca(NO3)2 . ·4H2O and 0.12 g of Mg(NO3)2 .6H2O was dissolved in 10 ml of deionized water and impregnated onto 2 g of hierarchical pore ZSM-5 molecular sieve. It was stirred at 25 °C for 8 h, then dried at 100 °C for 12 h, and subsequently calcined in air atmosphere at 550 °C for 3 h. The calcined catalyst was crushed and pressed into particles of 20 - 40 mesh. 0.5 g of the catalyst was loaded into a fixed-bed reactor and pretreated with nitrogen at 450 °C. When the reactor temperature dropped to 350 °C, a 20 wt% glycerol aqueous solution was introduced with a mass space velocity of 1.5 g·g -1 ·h -1 , the conversion rate of glycerol was 99%, the selectivity of acrolein was 91%, and the conversion rate greater than 95% was maintained for 500 hours. It was found by nitrogen physical adsorption analysis that the pore diameter of the hierarchical pore ZSM-5 molecular sieve was 23 nm, and the total content of the additives was 1 wt% (Ca and Mg each accounted for 0.5 wt%)
[0078] Example 9
[0079] 12 g of HZSM-5 molecular sieve (Si / Al = 30) was weighed and added to 360 ml of 0.3 mol / L NaOH solution. It was stirred at 65 °C for 30 min, centrifuged and washed until neutral, and dried at 100 °C for 12 h to obtain solid I; 8 g of solid I was added to 80 ml of 0.5 mol / L nitric acid solution, stirred at 60 °C for 5 h, then placed in an oven and dried at 100 °C for 12 h. The dried sample was calcined at 550 °C for 3 h to obtain solid II; 6 g of solid II was added to 120 ml of 1 mol / L NH4NO3 solution, and ion exchange was carried out 3 times at 85 °C, centrifuged and washed, dried at 100 °C for 12 h, and finally calcined at 550 °C for 3 h to obtain hierarchical pore ZSM-5 molecular sieve. 0.03 g of Zn(NO3)2 . 6H2O, 0.04 g of Ca(NO3)2 . 4H2O and 0.07 g of Mg(NO3)2 . 6H2O was dissolved in 10 ml of deionized water and impregnated onto 2 g of hierarchical pore ZSM-5 molecular sieve. It was stirred at 25 °C for 8 h, then dried at 100 °C for 12 h, and subsequently calcined in air atmosphere at 550 °C for 3 h. The calcined catalyst was crushed and pressed into particles of 20 - 40 mesh. 0.5 g of the catalyst was loaded into a fixed-bed reactor and pretreated with nitrogen at 450 °C. When the reactor temperature dropped to 350 °C, a 20 wt% glycerol aqueous solution was introduced with a mass space velocity of 1.5 g·g -1 ·h -1 , the conversion rate of glycerol was 98%, the selectivity of acrolein was 94%, and the conversion rate greater than 95% was maintained for 550 hours. It was found by nitrogen physical adsorption analysis that the pore diameter of the hierarchical pore ZSM-5 molecular sieve was 23 nm, and the content of the additives was 1 wt% (Zn and Ca each accounted for 0.34 wt%, Mg accounted for 0.32 wt%)
[0080] Comparative Example 1
[0081] The hierarchical pore ZSM-5 molecular sieve prepared in Example 1 was crushed and pressed into particles with a size of 20-40 mesh. 0.5 g of the particles was loaded into a fixed-bed reactor and pretreated with nitrogen at 450 °C. After the reactor temperature dropped to 350 °C, an aqueous solution of 20 wt% glycerol was introduced, and the mass space velocity was 1.5 g·g -1 ·h -1 . The conversion rate of glycerol was 89%, and the selectivity of acrolein was 80%.
[0082] Comparative Example 2
[0083] The hierarchical pore ZSM-5 molecular sieve prepared in Example 2 was crushed and pressed into particles with a size of 20-40 mesh. 0.5 g of the particles was loaded into a fixed-bed reactor and pretreated with nitrogen at 450 °C. After the reactor temperature dropped to 350 °C, an aqueous solution of 20 wt% glycerol was introduced, and the mass space velocity was 1.5 g·g -1 ·h -1 . The conversion rate of glycerol was 90%, and the selectivity of acrolein was 82%.
[0084] Comparative Example 3
[0085] The hierarchical pore ZSM-5 molecular sieve prepared in Example 3 was crushed and pressed into particles with a size of 20-40 mesh. 0.5 g of the particles was loaded into a fixed-bed reactor and pretreated with nitrogen at 450 °C. After the reactor temperature dropped to 350 °C, an aqueous solution of 20 wt% glycerol was introduced, and the mass space velocity was 1.5 g·g -1 ·h -1 . The conversion rate of glycerol was 90%, and the selectivity of acrolein was 82%.
[0086] Comparative Example 4
[0087] The hierarchical pore ZSM-5 molecular sieve prepared in Example 6 was crushed and pressed into particles with a size of 20-40 mesh. 0.5 g of the particles was loaded into a fixed-bed reactor and pretreated with nitrogen at 450 °C. After the reactor temperature dropped to 350 °C, an aqueous solution of 20 wt% glycerol was introduced, and the mass space velocity was 1.5 g·g -1 ·h -1 . The conversion rate of glycerol was 92%, and the selectivity of acrolein was 81%.
[0088] The above are only several embodiments of the present application, and do not impose any form of limitation on the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any person skilled in the art, without departing from the scope of the technical solution of the present application, making some changes or modifications using the disclosed technical content is equivalent to equivalent embodiments and all fall within the scope of the technical solution.
Claims
1. A molecular sieve catalyst, characterized in that, The molecular sieve catalyst includes a hierarchical pore molecular sieve and a promoter; The hierarchical pore molecular sieve is a hierarchical pore ZSM-5 molecular sieve; The pore size distribution of the hierarchical pore ZSM-5 molecular sieve is in the range of 10 - 30 nm; The promoter includes a promoter element selected from at least one of Zn, Mg, and Ca; The content of the promoter is 0.1 - 2 wt% of the mass of the molecular sieve catalyst.
2. A method for preparing the molecular sieve catalyst according to claim 1, characterized in that, It includes the following steps: The post-treated hierarchical pore ZSM-5 molecular sieve is added to an aqueous solution containing a promoter element precursor for impregnation, and then calcined I to obtain the molecular sieve catalyst; The post-treatment is a combined alkali treatment - acid treatment, including: the microporous ZSM-5 molecular sieve is subjected to alkali treatment in an alkali solution, dried I to obtain solid I; solid I is subjected to acid treatment in an acid solution, dried II and calcined II to obtain solid II; solid II is subjected to ion exchange in an ammonium salt solution, dried III and calcined III to obtain the hierarchical pore ZSM-5 molecular sieve.
3. According to the preparation method described in claim 2, characterized in that, The promoter element precursor is selected from at least one of Zn(NO3)2, Mg(NO3)2, and Ca(NO3)2; Preferably, the solid-liquid ratio of the hierarchical pore ZSM-5 molecular sieve to the aqueous solution containing the promoter element precursor is 1:2 - 1:10 g / ml.
4. According to the preparation method described in claim 2, characterized in that, The impregnation time is 5 - 24 hours, and the impregnation temperature is 20 - 50 °C; The temperature of calcination I is 400 - 600 °C, the time of calcination I is 1 - 6 hours, and the calcination I is carried out in an oxygen-containing atmosphere.
5. According to the preparation method described in claim 2, characterized in that, The silicon-aluminum ratio of the microporous ZSM-5 molecular sieve is Si / Al = 20 - 50.
6. According to the preparation method described in claim 2, characterized in that, The alkali solution is selected from one of KOH, NaOH, and Na2CO3; The concentration of the alkali solution is 0.1 - 0.4 mol / L; Preferably, the conditions of the alkali treatment include: stirring at 60 - 80 °C for 15 - 30 min; the temperature of drying I is 80 - 120 °C, and the time of drying I is 12 - 36 h.
7. According to the preparation method described in claim 2, characterized in that, The acid in the acid solution is selected from at least one of acetic acid, oxalic acid, hydrochloric acid, and nitric acid; The concentration of the acid solution is 0.1 mol / L - 2 mol / L; Preferably, the conditions of the acid treatment include: stirring at 60 - 100 °C for 2 - 8 h; The temperature of drying II is 100 °C, and the time of drying II is 10 - 24 h; The temperature of calcination II is 450 - 600 °C, and the time of calcination II is 2 - 5 h.
8. According to the preparation method described in claim 2, characterized in that, The ammonium salt in the ammonium salt solution is selected from one of NH4NO3 and NH4Cl; The concentration of the ammonium salt solution is 0.1 - 2 mol / L; Preferably, the temperature of drying III is 100 °C, and the time of drying III is 12 - 36 h; the temperature of calcination III is 450 - 600 °C, and the time of calcination III is 3 - 6 h.
9. A method for dehydrating glycerol to acrolein, characterized in that, A raw material containing an aqueous glycerol solution is introduced into a reactor and contacted with the catalyst for reaction; the catalyst is the molecular sieve catalyst described in claim 1.
10. According to the method described in claim 9, characterized in that, In the aqueous glycerol solution, the mass concentration of glycerol is 10 - 40 wt%; Preferably, the mass hourly space velocity of the raw material is 0.1 to 3.0 g·g -1 ·h -1 ; Preferably, the reaction temperature is 250 - 500 °C.
Citation Information
Patent Citations
Molecular sieve catalyst for catalyzing and dehydrating glycerin to prepare acraldehyde and preparation method of molecular sieve catalyst
CN103521256B
Hierarchical porous ZSM-5 zeolite catalyst for preparing acrolein through glycerin dehydration as well as preparation method and application of hierarchical porous ZSM-5 zeolite catalyst
CN103638965A
Cited By
Hierarchical pore molecular sieve for efficient depolymerization of industrial lignin as well as preparation and application of hierarchical pore molecular sieve
CN121609351A